Identification of Recent Ripple in Opak River Estuary, Kretek Subdistrict, Bantul Regency, Yogyakarta Special Region - Gunawan, Indra; Damayanti, Nabila Zafira; Astuti, Ella Dwi; Febrianti, Yeni; Rachmatullah P.P., Tegar Bagaskoro; Hutabarat, Ari Napas (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2024)
Ripple can be formed from various factors, namely wind, waves, currents, and tidal influences. The research area is located at the mouth of the Opak River, Kretek District, Bantul Regency, Yogyakarta Special Region with coordinates X: 421331 and Y: 9114347. This study aims to determine the factors that affect the formation of ripple and the dominance of factors that affect ripple at the mouth of the Opak River based on the calculation of the ripple index parameter. This research begins with a literature study to find strong theoretical basis. The data collected include wavelength (L), lee side length (LL), stoss side length (LS), maximum wavelength (Lmax), minimum wavelength (Lmin), mean wavelength (L), height (H), curved crestline length (CC), and deviation from straight line (d) and azimuth used to determine the general direction of the ripple. Then the calculation is carried out to obtain each ripple index parameter in the form of RI (Ripple index), PI1 (Parallelism Index 1), PI2 (Parallelism Index 2), SI (Straightness Index), RSI (Ripple Symmetrical Index), CI (Continuity Index) values. Based on data calculations, the results of the Ripple Index range from 0-20, Ripple symmetrical index ranges from 1-4. Parallelism index 1 ranges from 0-3, Parallelism index 2 ranges from 0-1, Straightness index ranges from 0-1.6. From the results of these calculations, it can be concluded that the ripple is affected by sea waves and the current of the Opak River.